The investigation of effects, signal pathways, and applications of high glucose on dental pulp stem cells - Shih-Yu Lee; I-Hsun Li; Wei-Cheng Tsai; Ming-Hua Ho; Chung-Hsing Li (Journal of Dental Sciences, 2025)
Background/purpose: Dental pulp stem cells (DPSCs) are among the most widely used dental-derived mesenchymal stem cells (MSCs), and their applications have involved various regions. The glucose metabolism plays a key role in cell function and the current literature presents conflicting evidence regarding the influence of glucose on MSCs' properties. This study evaluated the impact of high glucose (HG) on DPSCs. Materials and methods: DPSCs were stimulated with indicated concentrations of glucose. Cell viability was assessed using a cell counting kit, while apoptosis and autophagy were analyzed via western blot. MSCs immunophenotypic properties were determined by flow cytometry. Osteogenic, adipogenic, and neurogenic differentiation potential were evaluated using western blot, Alizarin red staining, oil red-O staining, and morphological analysis. Results: HG exposure led to a significant decrease in cell viability, with increased apoptosis and autophagy, as indicated by increased levels of cleaved caspase-3, cleaved poly (ADP-ribose) polymerase (PARP), and an elevated microtubule-associated protein 1 light chain 3 beta (LC3B)-II/LC3B-I ratio. However, the immunophenotypic characteristics of DPSCs remained unchanged. DPSCs also demonstrated enhanced osteogenic, adipogenic, and neurogenic differentiation potential by expressing Alizarin red and oil red-O staining, neural-like cell morphology, and several differentiation-related proteins after HG culture stimulation. Conclusion: The present study demonstrated that while HG slightly impairs DPSC viability, it promotes osteogenic, adipogenic, and neurogenic differentiation. Providing valuable insights into the mechanisms by which HG influences various differentiation pathways in DPSCs and establishes a foundation for potential clinical applications of DPSCs in regenerative medicine for diabetic patients.